Lung Health of Early COPD (LHEC): A Multi-Center Cohort Study—Rational and Design - Li W; Lei J; Li B; Tang X; Peng Y; Huang K; Yang T (International Journal of COPD, 2025)
Wei Li,1 Jieping Lei,1,2 Baicun Li,1,3 Xingyao Tang,1,4 Yaodie Peng,1,5 Ke Huang,1 Ting Yang1 1National Center for Respiratory Diseases; State Key Laboratory of Respiratory Health and Multimorbidity; National Clinical Research Center for Respiratory Diseases; Institute of Respiratory Medicine, Chinese Academy of Medical Sciences; Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 2Department of Clinical Research and Data Management, Center of Respiratory Medicine, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 3National Center for Respiratory Medicine Laboratories, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 4Capital Medical University, Beijing, People’s Republic of China; 5Peking University China-Japan Friendship School of Clinical Medicine, Beijing, People’s Republic of ChinaCorrespondence: Ke Huang, National Center for Respiratory Diseases; State Key Laboratory of Respiratory Health and Multimorbidity; National Clinical Research Center for Respiratory Diseases; Institute of Respiratory Medicine, Chinese Academy of Medical Sciences; Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital, No. 2, East Yinghua Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Tel +86 010-84206273, Email huangke_zryy@163.com Ting Yang, National Center for Respiratory Diseases; State Key Laboratory of Respiratory Health and Multimorbidity; National Clinical Research Center for Respiratory Diseases; Institute of Respiratory Medicine, Chinese Academy of Medical Sciences; Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital, No. 2, East Yinghua Road, Chaoyang District, Beijing, 100029, People’s Republic of China, +86 010-84206276, Email zryyyangting@163.comIntroduction: Little is known about the early stage of chronic obstructive pulmonary disease (COPD), especially in nonsmokers. More efforts should be made to investigate the characteristics of this stage, as well as to identify biomarkers for early diagnosis. This study aimed to build a national cohort of patients with early COPD in China to address the current research gaps in this area.Methods and Analysis: We intend to enroll 1500 participants aged 35 to 75 years with post-bronchodilator spirometry showing a forced expiratory volume in one second (FEV1)/forced vital capacity ratio below 0.8 and an FEV1% predicted of at least 80%, classified as early COPD subjects. Recruitment will take place across 24 centers located in various provinces throughout China. Participants will be categorized into four groups based on their smoking status and spirometry results: pre-COPD smokers, mild COPD smokers, pre-COPD nonsmokers, and mild COPD nonsmokers. Each participant will undergo three visits over a 2-year period, including one baseline visit and two follow-up visits. Comprehensive and follow-up questionnaires will be administered, and the participants will undergo physical examination, pulmonary function testing, high-resolution computed tomography (CT), routine blood tests, and biological sample collection. We will analyze the changes in lung function, CT images, symptoms, biomarkers, and other relevant parameters across the different groups.Discussion: There is an urgent need for a more precise definition of early COPD for intervention at an earlier stage. By setting a narrower range of lung function thresholds to define pre- and mild-COPD, this study will effectively observe the early disease progression of COPD patients in a shorter period of time. By including a considerable proportion of nonsmokers, this study is more likely to identify new factors influencing early COPD.Ethics and Dissemination: Ethical approval was obtained China–Japan Friendship Hospital (Beijing, PR China; approval number 2022-KY-141). Participants will provide written informed consent. Study findings will be disseminated through conferences and peer-reviewed scientific and professional journals.Trail Registration Number: NCT05466396.Keywords: early stage, non-smoking, mild-COPD, pre-COPD, protocol